NEW NORMAL IMPLEMENTATION IN RT 04 RW 14 KALIRUNGKUT, SURABAYA CITY BASED ON SURABAYA - Tukiman - -; Shinta Devi Apriliana; Vina - Nahdiyah; Tentra - Olivia (Universitas Madura, 2020)
Implementation of policies related to the prevention and spread of covid-19 is needed as a form of vigilance against covid-19 virus outbreaks. One area that is implementing is the city of Surabaya by implementing Perwali Number 28 of 2020 Regarding the Guidelines for the New Normal Order in the 2019 Corona Virus Diaseas Pandemic Conditions (Covid-19) in Surabaya City. In preventing the spread of Covid-19, a foundation is needed in carrying out the implementation of the Surabaya Mayor's policy. It is expected that the participation between the Government in this case the Mayor of Surabaya and the Community can be carried out properly in line with the enactment of the regulation. Concrete manifestation of the implementation of the policy is the existence of a formidable village program as one of the intermediary programs of the policy of the Mayor of Surabaya. The purpose of this study was to identify and analyze the New Normal Implementation in RT 04 RW 14 Kalirungkut, Surabaya City Based on Perwali Number 28 Tahun 2020. The type of research in this study is qualitative with descriptive methods. The technique of determining informants is by means of purposive sampling by collecting data information in the form of primary data and secondary data. Which is primary or direct data obtained from interviews and observations. While secondary data obtained from various references such as books and journals that support this research. The results showed that the implementation factors were communication, resources, disposition, and bureaucratic structure. Of the four factors, the implementation of Surabaya Mayor Regulation No. 28 has been implemented, although it has not been maximized. Resilient village program as a program of the policy is also carried out in accordance with the standard operating procedures specified in the regulation.